Monitoring Iklim Mikro pada Greenhouse Secara Real Time Menggunakan Internet of Things (IoT) Berbasis Thingspeak - Anri Kurniawan; Andika Ristiono; Slamet Sulistiadi (The University of Lampung, 2021)
Farm cultivation in the highlands is constrained by the long rainy season, less efficient sunlight and susceptible to pests and diseases. One of the solutions in cayenne pepper cultivation is using hydroponics and greenhouse s to minimize pests and diseases that come from the soil and are carried by the wind. The purpose of this research is to produce